Desmoplastic Reaction, Immune Cell Response, and Prognosis in Colorectal Cancer - Akimoto, Naohiko; Väyrynen, Juha P.; Zhao, Melissa; Ugai, Tomotaka; Fujiyoshi, Kenji; Borowsky, Jennifer; Zhong, Rong; Haruki, Koichiro; Arima, Kota; Lau, Mai Chan; Kishikawa, Junko; Twombly, Tyler S.; et al. (Frontiers in Immunology, 2022)
Background: The relationships between tumor stromal features (such as desmoplastic reaction, myxoid stroma, and keloid-like collagen bundles) and immune cells in the colorectal carcinoma microenvironment have not yet been fully characterized. Methods: In 908 tumors with available tissue among 4,465 incident colorectal adenocarcinoma cases in two prospective cohort studies, we examined desmoplastic reaction, myxoid stroma, and keloid-like collagen bundles. We conducted multiplex immunofluorescence for T cells [CD3, CD4, CD8, CD45RO (PTPRC), and FOXP3] and for macrophages [CD68, CD86, IRF5, MAF, and MRC1 (CD206)]. We used the inverse probability weighting method and the 4,465 incident cancer cases to adjust for selection bias. Results: Immature desmoplastic reaction was associated with lower densities of intraepithelial CD3+CD8+CD45RO+ cells [multivariable odds ratio (OR) for the highest (vs. lowest) density category, 0.43; 95% confidence interval (CI), 0.29-0.62; Ptrend <0.0001] and stromal M1-like macrophages [the corresponding OR, 0.44; 95% CI, 0.28-0.70; Ptrend = 0.0011]. Similar relations were observed for myxoid stroma [intraepithelial CD3+CD8+CD45RO+ cells (Ptrend <0.0001) and stromal M1-like macrophages (Ptrend = 0.0007)] and for keloid-like collagen bundles (Ptrend <0.0001 for intraepithelial CD3+CD8+CD45RO+ cells). In colorectal cancer-specific survival analyses, multivariable-adjusted hazard ratios (with 95% confidence intervals) were 0.32 (0.23-0.44; Ptrend <0.0001) for mature (vs. immature) desmoplastic reaction, 0.25 (0.16-0.39; Ptrend <0.0001) for absent (vs. marked) myxoid stroma, and 0.12 (0.05-0.28; Ptrend <0.0001) for absent (vs. marked) keloid-like collagen bundles. Conclusions: Immature desmoplastic reaction and myxoid stroma were associated with lower densities of tumor intraepithelial memory cytotoxic T cells and stromal M1-like macrophages, likely reflecting interactions between tumor, immune, and stromal cells in the colorectal tumor microenvironment.